The determinants of bank liquidity: An empirical study on Chinese banks - YANG, JIALI (2014)
Liquidity risk is considered to be inherent due to banks’ transformation functions. It determines a bank’s solvency and makes bank vulnerable to unexpected cash outflows. If not well managed, this risk will cause considerable loss to banks or even lead to bankruptcy. With the destructive effect of liquidity risk verified in the 2007 financial crisis, managing liquidity risk becomes one of the major tasks of worldwide commercial banks.This dissertation investigates the determinants of liquidity in Chinese banks to identify some practical ways of liquidity risk management. Particularly, intra-industry differences regarding the determinants will be examined. Throughout the whole empirical part, a quantitative method will be applied, including simple ratio analysis and panel data regression. Consequently, it is found that intra-industry differences do exist while big banks and small banks in China have different factors of liquidity. Besides, distinct from bank liquidity in other western countries, liquidity in Chinese banks shows no significant relationship with macro factors such as GDP. It is expected that these empirical results would provide some implications for banks and regulators in monitoring and controlling liquidity risk to some extent.